An earthquake reality: fasciotomy wounds and treatments - Erdoğan, Hakan; Oto, Arzu; Yerci, Gamze; Koçer, Gülcan; Menekşe, Burcu; Aktürk, Berna; Yıldırım, Ümit; Elmas Bozdemir, Şefika (The European Research Journal, 2024)
Earthquake-induced Crush Syndrome and subsequent acute kidney injury are important issues that affect morbidity and mortality. Fasciotomies prolong the length of stay in intensive care unit in patients with Compartment Syndrome due to the complications it causes. Infections and delayed wound healing are two common complications among these. Therefore, early closure of fasciotomy wounds is recommended. Although different treatments can be applied for treatment of wounds, data on this subject in pediatric patients are insufficient. We report the case of a 15-year-old girl who developed acute renal failure due to crush syndrome after being trapped in the wreckage for 9 hours and undergoing fasciotomy procedures for four locations, in the left extremity, two in the thigh and two in the cruris. Hemodialysis, antihypertensive, and antibiotic treatment were administered during the intensive care follow-up due to acute kidney injury, hypertension, and sepsis. With negative pressure therapy, silver alginate wound dressing, and hyperbaric oxygen therapy, all wounds epithelialized within two months. However, rehabilitation for drop foot syndrome caused by nerve cuts in the left extremity continues.